Non-radioactive detection of 17p11.2 duplication in CMT1A: a study of 78 patients. Issue 11 (November 1994) - Schiavon, F; Mostacciuolo, M L; Saad, F; Merlini, L; Siciliano, G; Angelini, C; Danieli, G A
Abstract : Charcot-Marie-Tooth disease type 1 (CMT1) is a peripheral neuropathy characterised by progressive distal muscular atrophy and sensory loss with markedly decreased nerve conduction velocity, mostly inherited as an autosomal dominant trait. The most common form, type 1A, is associated with a 1.5Mb DNA duplication in region p11.2-p12 of chromosome 17 in many patients. In this study a non-radioactive test for detection of the CMT1A duplication based on an RM11-GT microsatellite polymorphism is presented. Although different methods have been devised for this purpose, the present method has the advantage of being rapid, informative, economical, easily interpretable, and, therefore, it represents a very useful tool for diagnosis of CMT1A, especially before clear manifestation of clinical symptoms. Seventy-eight patients diagnosed clinically as having CMT and evaluated by electrophysiological methods were tested with an RM11-GT microsatellite and with probe pVAW409R3. The CMT1A duplication was found in 76% of the 56 unrelated patients. RM11-GT was the most informative marker with a heterozygosity of 89%.